Drivers leading Olympic Athletes to Entrepreneurial Opportunities: An Analysis of the US Olympic Team from Tokyo 2020 - Abuzeni, J.; Obodnikovs, K. (2022)
Background: The authors have observed that Olympic athletes of Team USA supplement their income, or finance themselves entirely, through entrepreneurial opportunities. This study focuses on Olympic Athletes from the United States - with a limitation to members of the US Olympic Rowing Team that competed at the Tokyo 2020 Olympic Games. Unbeknownst to many, athletes from Team USA, and Olympians globally, do not receive compensation from the International Olympic Committee (IOC) to compete at the Olympic Games. Instead, US Olympians receive a monthly stipend from the United States Olympic and Paralympic Committee (USOPC) ranging between $1000 to $2000 US Dollars. Provided this information, the authors were interested in identifying whether their financial situation, or any other drivers, made them more likely to pursue entrepreneurial opportunities.